2011
DOI: 10.1002/jssc.201100597
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymer composed of cationic backbone and bottle brush‐like side chains as a physically adsorbed coating for protein separation by capillary electrophoresis

Abstract: To stabilize electroosmotic flow (EOF) and suppress protein adsorption onto the silica capillary inner wall, a cationic hydroxyethylcellulose-graft-poly (poly(ethylene glycol) methyl ether methacrylate) (cat-HEC-g-PPEGMA) graft copolymer composed of cationic backbone and bottle brush-like side chains was synthesized for the first time and used as a novel physically adsorbed coating for protein separation by capillary electrophoresis. Reversed (anodal) and very stable EOF was obtained in cat-HEC-g-PPEGMA-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Because of the versatility of ATRP, pOEGMA can also be incorporated into substantially more architecturallycomplex structures by synthesis from well-defined multifunctional macro-initiators, thereby producing socalled "bottlebrush" or double-branched architectures [40][41][42][43]. Yamamoto et al [44] have performed a detailed investigation of the temperature-responsiveness of such bottlebrush polymers composed of pOEGMA homo-/copolymers grafted to poly(2-(2-bromoisobutyryloxy)ethyl methacrylate) (PBIEM) (Fig.…”
Section: Complex Structuresmentioning
confidence: 99%
“…Because of the versatility of ATRP, pOEGMA can also be incorporated into substantially more architecturallycomplex structures by synthesis from well-defined multifunctional macro-initiators, thereby producing socalled "bottlebrush" or double-branched architectures [40][41][42][43]. Yamamoto et al [44] have performed a detailed investigation of the temperature-responsiveness of such bottlebrush polymers composed of pOEGMA homo-/copolymers grafted to poly(2-(2-bromoisobutyryloxy)ethyl methacrylate) (PBIEM) (Fig.…”
Section: Complex Structuresmentioning
confidence: 99%
“…The authors reported that polybrene‐dextran sulfate‐polybrene coating offered long‐term stability with migration time RSD values of 1.6% and peak area RSD values of 9%. Other cationic polymers have also been evaluated as coating agent for the analysis of basic proteins, such as hydroxyethylcellulosegraft‐poly(PEG methyl ether methacrylate) (cat‐HEC‐g‐PPEGMA), and showed variability from capillaries to capillaries of <3% RSD for migration times across a wide range of pH, as well as better separation for neutral and acidic proteins compared to bare‐fused silica capillaries . However, cationic polymers such as polybrene‐based tend to result in higher pH‐independent EOF leading to poorer resolution and separation of compounds .…”
Section: Ce‐ms For Proteomic Analysismentioning
confidence: 99%
“…Static (permanent) modifications of the inner capillary wall involve covalent bonding or strong physical adsorption of the synthetic and natural polymers, such as polyacrylamide, PVA, PEG, linear and grafted cellulose derivatives , brush‐like copolymer , or cationic triblock copolymer . In addition to suppression of wall adsorption, dynamic and/or permanent capillary coatings are used also for control of the EOF, which influences separation efficiency, resolution, and speed of CE analyses of all types of analytes, including peptides and proteins.…”
Section: Suppression Of Adsorption and Control Of Eofmentioning
confidence: 99%